2020
DOI: 10.1177/0042098020903248
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal segmenting of urban workplaces: The gendering of multi-locational working

Abstract: Existing urban research has focused on gender differences in commuting patterns to and from homes, but has paid little attention to the gendered diversity in the spatiotemporal patterns of work. The increase in remote working and information and communications technology (ICT) work has been emphasised, but at the cost of exploring the full range of workplaces and multilocational working observed in urban areas. This article develops a new classificatory system to analyse the spatiotemporal patterns of work in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…These differences in working at or from home are unlikely to be solely sectorial effects. Burchell et al (2020) found that within European urban areas there is a significantly greater likelihood of working from home in Scandinavian countries (including in Sweden for which we do not have data in Figure 1) and a lower likelihood in the Mediterranean and transitional countries when industry sectors were held constant. It is much more likely that high proportions of workers who can potentially work at or from home coincides with national policies of flexible working and gender equality legislation.…”
Section: Spatial Inequalities Of Working At Homementioning
confidence: 70%
See 1 more Smart Citation
“…These differences in working at or from home are unlikely to be solely sectorial effects. Burchell et al (2020) found that within European urban areas there is a significantly greater likelihood of working from home in Scandinavian countries (including in Sweden for which we do not have data in Figure 1) and a lower likelihood in the Mediterranean and transitional countries when industry sectors were held constant. It is much more likely that high proportions of workers who can potentially work at or from home coincides with national policies of flexible working and gender equality legislation.…”
Section: Spatial Inequalities Of Working At Homementioning
confidence: 70%
“…Prior to the COVID-19 pandemic, telecommuting was largely implemented as a flexible working arrangement to enhance worker productivity and well-being (Menezes and Kelliher, 2011). However, as the term ‘telecommuting’ implies, the ability to work from or at home is associated with the high use of information and communication technologies (Burchell et al, 2020; Ojala and Pyöriä, 2017) and therefore varies substantially across sectors. Jobs in financial, professional, and technical services are more likely to be performed at or from home as communication with co-workers and customers can be done electronically.…”
Section: Social Inequalities Of Working At Homementioning
confidence: 99%
“…Burchell et al (2021) also use a novel concept of workplace location that measures where people work and how often they work in a particular type of place, including the home, employers’ premises and public spaces. This concept is less detailed than the one suggested by Shearmur (2021), but is able to sufficiently capture the concept of ‘multi-locality’, which the authors can measure on a daily, weekly or monthly basis.…”
Section: Contributions To the Special Issuementioning
confidence: 99%
“…3% of employees are estimated to have worked exclusively from home pre-COVID-19 (Reuschke and Felstead, 2020). This proportion was lower still in urban areas where people rather worked sometimes but not all of their time from home (Burchell et al, 2020).…”
Section: Homeworking Intensity and City-regionsmentioning
confidence: 86%
“…This regional variation in the prevalence of homeworking is related to occupational and industrial disparities. Since working at home is facilitated by technological connectivity, its take-up varies by occupational characteristics (Burchell et al, 2020). Jobs in financial, professional, and technical services are more likely to be performed at home in contrast to high service and labour-intensive work (Felstead and Henseke, 2017).…”
Section: Regional and Occupational Disparities In Homeworkingmentioning
confidence: 99%